Efektivitas Follicle Stimulating Hormone (FSH) terhadap Produktivitas dan Siklus Bertelur Ayam Lokal (EFFECTIVENESS OF FOLLICLE STIMULATING HORMONE (FSH)ON THE PRODUCTIVITY AND EGG LAYING CYCLE OF THE DOMESTIC FOWL) - Omega, Maria Prihtamala; Maheshwari, Hera; Widjajakusuma, Reviany (Jurnal Veteriner, 2016)
Abstak dapat dibaca pada Full Text Abstract can be read at Full Text
Keywords: FSH; productivity; egg laying cycle